2011
DOI: 10.1192/bjp.bp.109.075622
|View full text |Cite
|
Sign up to set email alerts
|

Initiatives to shorten duration of untreated psychosis: systematic review

Abstract: How early detection can be achieved is not clear. Evidence is most promising for intensive public awareness campaigns: these require organisation and resourcing at a regional or national level. More good-quality studies are needed to address gaps in knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 46 publications
3
137
0
2
Order By: Relevance
“…Evidence for the effectiveness of such programmes in reducing DUP is patchy. 132 However, the ENRICH studies found that measurement of DUP alone does not capture the complexity of help-seeking in psychotic disorders and does not help elucidate critical BME differences in pathways to care. Rather than universal public education campaigns, researchers and practitioners need to develop public awareness programmes that are specifically focused on BME groups and test whether help-seeking pathways such as faith encounters can be targeted for reducing treatment delays and preventing adverse pathways.…”
Section: Do Black and Minority Ethnic Groups Mistrust Mental Health Smentioning
confidence: 99%
“…Evidence for the effectiveness of such programmes in reducing DUP is patchy. 132 However, the ENRICH studies found that measurement of DUP alone does not capture the complexity of help-seeking in psychotic disorders and does not help elucidate critical BME differences in pathways to care. Rather than universal public education campaigns, researchers and practitioners need to develop public awareness programmes that are specifically focused on BME groups and test whether help-seeking pathways such as faith encounters can be targeted for reducing treatment delays and preventing adverse pathways.…”
Section: Do Black and Minority Ethnic Groups Mistrust Mental Health Smentioning
confidence: 99%
“…However, reducing DUP using community education and awareness campaigns has met with mixed results, 11 with evidence suggesting that neither general practitioner (GP) education 12 nor dedicated early intervention services (EIS) 13 by themselves reduce DUP or generate more treated cases. In exploring the reasons for these mixed findings, it has been argued that attention should be given to the component delays that contribute to DUP, such as individual help-seeking delays and delays within services, as well as its total duration.…”
mentioning
confidence: 99%
“…Drake et al 2000 ;Clarke et al 2006) and our findings regarding the relationship of DUP and DUI to longer-term outcomes are comparable with another study based on a nonspecialized program (Crumlish et al 2009). Furthermore, there is very limited evidence that the efforts of early intervention programs, including ours, to reduce treatment delay are effective in changing the distribution of DUP (Malla et al 2005 ;Lloyd-Evans et al 2011).…”
Section: Discussionmentioning
confidence: 98%